Prevalence of Valvular Heart Disease and Pulmonary Hypertension in Children in Rantau-Prapat City, North Sumatra, Indonesia - Haykal, Teuku Bob; Sitepu, Andika; Ilyas, Kamal Kharrazi (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Background: Valvular heart disease and pulmonary hypertension (PH) are two distinct but often interconnected cardiac conditions that can affect children and encompass abnormalities of the heart's valves such as the aortic, mitral, tricuspid, and pulmonary valves, and can present with symptoms such as chest pain, fatigue, and dyspnea. In contrast, PH refers to elevated blood pressure in the pulmonary arteries. Routine screening for these conditions is needed for prompt diagnosis and management. This study was conducted to obtain data on children with valvular heart disease or PH who participated in the Community Service Program of the Department of Cardiology and Vascular Disease, Universitas Sumatera Utara. Method: This study was a descriptive study conducted through a cross-sectional study design. Data was collected from interviews and on-the-spot examination with validated measurement tools. Data was analyzed using SPSS version 26. Categorical variables were presented using frequency (n) and percentage (%), and numerical variables with normally distributed data were presented with mean and standard deviation (SD). In non-normally distributed data, numerical variables were presented using the median and interquartile range. Results: There were 157 children included in this study. Most subjects were female (n=94, 59.9%) in the age range 12 to 16 years old. Most subjects (n=152, 96.8%) had normal mitral valves, three subjects had anterior mitral valve prolapse (1.9%), one subject (0.6%) had anterior mitral valve thickening and one subject (0.6%) had mild mitral regurgitation. 10 subjects (5.7%) had pulmonary regurgitation. Two subjects had tricuspid regurgitation (1.2%). No subjects had any aortic abnormalities. No subjects had a PH. Conclusion: In the children population in Rantau-Prapat City, most subjects with valve abnormalities had mitral and pulmonary valve abnormalities. No subjects had aortic valve abnormalities or PH.